Low-level laser therapy reduces the fatigue index in the ankle plantar flexors of healthy subjects. Issue 9 (December 2016) - Souza, Clécio; Borges, Daniel; Brito Macedo, Liane; Brasileiro, Jamilson
Abstract Low-level laser therapy (LLLT) has been suggested as a resource capable of increasing resistance to fatigue and enhancing muscle performance through its metabolic and photochemical effects. This study evaluated the immediate effects of the application of LLLT on neuromuscular performance of the plantar ankle flexors in healthy subjects through a fatigue-induced protocol. This is a randomized controlled clinical trial, attended by 60 young and physically active volunteers of both genders. The subjects were randomly assigned into three groups, control, placebo, and laser, and underwent a preliminary evaluation of the isokinetic performance of plantar flexors and electromyographic activity of the soleus muscle to ensure homogeneity between groups. After the application of the respective intervention protocols, participants were induced to fatigue by performing 100 isokinetic concentric contractions of ankle plantar flexors at a speed of 90°/s. The dynamometric fatigue index (DFI) and median frequency were recorded during the fatigue protocol for comparison between groups. The group receiving the laser application showed significantly lower dynamometric fatigue index (p  = 0.036) when compared to control and placebo groups. In relation to the median frequency during the fatigue test, there was a decrease in all groups, however with no differences between them. We suggest that LLLT being applied prior to exercise can reduce the fatigue index in the ankle plantar flexors of healthy subjects.